The Flipped Classroom Model in German for Hospitality: A Classroom Action Research in The FB Service Study Program - Susianti, Hartanti Woro; Sutama, I Made; Dewantara, I Putu Mas; Wirahyuni, Kadek (Interference: Journal of Language, Literature, and Linguistics, 2025)
Abstract. German language learning at Bali Tourism Polytechnic (BiTP), particularly in reading skills, often faces challenges in effectiveness and student engagement. Students tend to passively receive material in class and lack motivation to develop reading skills independently. This study aims to improve German reading skills and foster independent learning motivation through the Flipped Classroom model. Using Classroom Action Research (CAR), the study examines the model’s application in teaching "Deutsch im Restaurant," focusing on reading skills. Research instruments include participatory observation, reading tests, motivation questionnaires, and lecturer reflection notes. Conducted in 5th-semester Food and Beverage Service classes, the study followed Poltekpar Bali’s daily schedule. The approach allows students to study materials at home via readings and videos, maximizing class time for discussions and deeper comprehension. The results demonstrate that the Flipped Classroom model is effective in improving German reading skills, with significant enhancements in text comprehension and active student participation. The implementation of this method also successfully increased students' independent learning motivation. The global implication of this research is the potential for the Flipped Classroom model to be adapted in other foreign language learning contexts, particularly in enhancing reading skills and self-directed learning across various educational institutions. However, the application of the Flipped Classroom model also presents challenges, such as varying levels of independent learning abilities among students. Therefore, lecturers need to prepare materials thoroughly and provide clear guidance to ensure all students can optimally benefit from this method. Keywords: Deutsch im Restaurant, Flipped Classroom, Reading Skills